MUTATION DETECTION OF MULTIDRUG-RESISTANT TUBERCULOSIS BY RT-PCR METHOD AS THE DIAGNOSTIC TOOL OF MDR-TB - Titta Novianti; alfero Putra Iryanto; feby feby; callista marsya; putri mega utami; febriana dwi wahyuni; henny saraswati; seprianto; adri nora; roaslein putri; nie nie; sabar pambudi (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2023)
Eight percent of tuberculosis (TB) cases worldwide are resistant to rifampicin, with mutations occurring in the rpoB and katG genes. It is necessary to develop a specific multidrug-resistant (MDR) diagnostic technique using the RT-PCR method in Indonesia to aid in rapid and accurate diagnosis. In-silico testing using SnapGene software resulted in the design of DNA primers for the katG and rpoB genes, plasmids, and specific probes. This study employed a cross-sectional design using 30 non-MDR-TB and MDR-TB samples from RSUD Sitanala, Tangerang Banten, which were tested for amplification of the katG and rpoB genes using Sybr green RT-PCR. Validity testing was conducted using specific probes for the katG and rpoB genes. The amplification results showed that MDR-TB samples and MDR-TB plasmids required a longer time compared to non-MDR-TB samples and non-MDR-TB plasmids. The Quantification Cycle (Cq) value in non-MDR-TB samples was lower than the Cq value in MDR-TB samples. A t-test revealed a significant difference in Cq values of the rpoB and katG genes between MDR-TB and non-MDR-TB patients (p-value < 0.005). These differences in Cq values indicate that the findings of this study can serve as an initial reference for the development of an RT-PCR-based diagnostic kit for MDR-TB.